2014
DOI: 10.7863/ultra.33.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Sonographic Assessment of Placental Volume and Vascularization in Pregnancies Complicated by Hypertensive Disorders

Abstract: Pregnancies complicated by hypertensive disorders are associated with reduced placental vascularity but not with reduced placental volumes. These findings are independent of changes in uterine artery Doppler studies. Future studies of the prediction of preeclampsia may focus on placental vascularity in combination with results of Doppler studies of the uterine arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In GHT and PE group, both VI and FI were significantly lower (26), as a proof of placental maldevelopment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In GHT and PE group, both VI and FI were significantly lower (26), as a proof of placental maldevelopment.…”
Section: Discussionmentioning
confidence: 90%
“…Because of the chronic intrauterine hypoxia the placental alterations are presented from first trimester Similarly to previous first trimester findings (26). In case of hypertensive disorders of pregnancy (CHT, GHT or PE) placental vascularization, which is characterized by FI, is significantly lower compared to NBP cases in the second and third trimesters, and it becomes even more affected when hypertension is associated with gestational diabetes (CHT+GDM, GHT+GDM) and correlated with the lenght of pathological lenght of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the increase in VI noted in women with CH may represent a placental response ─ elevated vascularization rate ─ to increased maternal blood pressure and hypothesised that the reduction in FI seen throughout the groups reflected impaired perfusion in the placenta [34]. Within obese cohorts, it has been suggested that flow indices are relatively unreliable for prediction of PE [9], and that future research should focus only on the role of vascularization indices (VI and VFI) [9,36]. Flow indices are depth dependent and, in the obese population, there is an increased distance from the placenta to the abdominal surface which may influence performance of FI.…”
Section: Discussionmentioning
confidence: 99%
“…This influence probably occurs because the number of vessels is affected, whereas the flow is not affected in this specific point of gestation. Studies that have evaluated placental vascularization in the first trimester and have predicted pregnancy complications observed that women with diminished VI and VFI showed an increased tendency to have pregnancies that were later complicated with preeclampsia and fetal growth restriction (de Almeida Pimenta et al 2014; Odeh et al 2011; Odibo et al 2011). Short-term exposure to air pollution seems to affect the same indexes, which indicates the possible pathway by which air pollution may provoke these complications (Olsson et al 2013; Pedersen et al 2014; Romão et al 2013; Sapkota et al 2012; Shah et al 2011; van den Hooven et al 2011; Yorifuji et al 2015).…”
Section: Discussionmentioning
confidence: 99%